PEMBELAJARAN MELALUI ULASAN: ANALISIS KRITIS MAHASISWA TERHADAP BUKU FIKSI DAN NONFIKSI - Sukawati, Sary; Zenab , Ai Siti (STKIP Siliwangi, 2024)
Learning through reviews can provide space for students to demonstrate critical analysis skills in reading and writing reviews. This research aims to: 1) describe the effectiveness of review learning on students' critical analysis of fiction and non-fiction books, 2) determine the extent to which students are able to apply critical analysis skills in writing reviews of fiction and non-fiction books. The research method used is descriptive quantitative with data collection techniques through observation, questionnaires and tests. The object of the research is data from writing review texts by 1st semester students of the D4 Department of Health Promotion, Poltekkes Kemenkes Bandung. The research results show that the activity of writing fiction and non-fiction book reviews is effective in developing students' critical analysis skills. Review activities include five stages: 1) orientation, 2) synopsis/summary, 3) analysis, 4) evaluation, and 5) conclusion. The results of students' critical analysis skills showed an average score of 90.37 in fiction and 84.71 in non-fiction. Thus, it can be concluded that the activity of writing fiction and non-fiction book reviews has the potential to make a positive contribution to the development of critical analysis skills for students.